Legal Politics of Increasing Welfare Based on Strengthening the Manufacturing Industry in Central Java - Muhammad Ardhi Razaq Abqa; Faris Apriyadi; Arnanda Yusliwidaka (Universitas of Muhammadiyah Makassar, 2022)
The background of this research is that people's welfare and regional development in Central Java have not increased. This is a very serious problem that needs to be properly addressed. The Indonesian constitution mandates in the preamble of paragraph 4 that the state aims to advance public welfare. This study aims to contribute ideas, namely legal politics, to increase welfare based on strengthening the manufacturing industry in Central Java. This study uses a normative juridical method with a statutory and conceptual approach. The results of this study are that to increase welfare based on strengthening the manufacturing industry in Central Java, at least ten choices of legal politics (policies) are needed, namely; legal harmonization, reforming the bureaucracy, optimizing the risk management team, optimizing cooperation with the private sector, maintaining economic commodities, sustainable infrastructure development, optimizing technology and industrial digitization, maintaining energy availability, holding national and international scale exhibitions, establishing special areas for development research. Recommendations in this study; researchers must conduct research related to increasing welfare through the manufacturing industry because there is still very little literature that can provide additional insight for society in general and for stakeholders and industrial digitization, maintaining energy availability, organizing national and international scale exhibitions, establishing special areas for development research. Recommendations in this study; researchers must conduct research related to increasing welfare through the manufacturing industry because there is still very little literature that can provide additional insight for society in general and for stakeholders and industrial digitization, maintaining energy availability, organizing national and international scale exhibitions, establishing special areas for development research. Recommendations in this study; researchers must conduct research related to increasing welfare through the manufacturing industry because there is still very little literature that can provide additional insight for society in general and for stakeholders.